Mapeamento de competências do coordenador de curso de graduação da UFPB - Medeiros, Alesandra Bandeira Porfírio (2019)
Academic management is characterized as an activity inherent in the work of the university professor, who, in addition to the activities related to the institution's end-activity, teaching, research and extension, is entrusted with managerial activities that have little or no relation to their academic background. The present research aims to map the necessary skills to the academic-manager for the exercise of the coordinator of graduation course of the UFPB. The literature on the mapping of competences provides a theoretical and methodological basis for conducting research on individual competencies and their alignment with the institution's strategic objectives. Methodologically, this research is characterized as descriptive, of an applied nature, of qualitative approach, whose script was defined based on the mapping of competences, an important instrument of the Management System by Competencies. As a means of investigation, we used bibliographic, documentary and field research. The methodological procedures were based on documentary analysis, interviews with teachers representing the group of course coordinators, and content analysis. The analysis of the knowledge, skills and attitudes (CHA) presented by the interviewees allowed the distinction of different dimensions related to the functions of the course coordinator, which involve specific groups of CHA. These dimensions are perceived in different groups of attributions and responsibilities of the academic manager, so that this group seeks to differentiate the resources of competences, that is, knowledge, ability and attitudes, focused on each of these dimensions. For each dimension, competencies were listed, in terms of expected performance, as well as the competence resources pointed out by the interviewees. Competencies related to the following dimensions were grouped: pedagogical / academic, managerial, institutional, political, socioemotional and technical / technological. The results of the research can be used to, among other purposes, the planning of the Program of Training of Managers of Academic Units within the scope of the UFPB, provided for in Resolution 23/2012 / CONSUNI / UFPB.